2018
DOI: 10.1039/c8nj03342k
|View full text |Cite
|
Sign up to set email alerts
|

The linear relationship derived from the deposition potential of Pb–Ln alloy and atomic radius

Abstract: Lanthanides possess extremely similar properties because their radius only changes slightly due to lanthanide contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It had Through the condensation and summarization of the atomic radius of the lanthanides and the equilibrium potentials data in Table I, it is found that there is a profoundly interwoven between them, and based on our research team, it is found that Sn, Pb and Al were used as the active cathode, and there was a mathematical equation for the equilibrium potential and atomic radius of the alloy compounds formed with the lanthanides. [42][43][44] Further research shows that the equation could predict the equilibrium potentials of Al-An alloy compounds when Al as substrate metal. Therefore,…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It had Through the condensation and summarization of the atomic radius of the lanthanides and the equilibrium potentials data in Table I, it is found that there is a profoundly interwoven between them, and based on our research team, it is found that Sn, Pb and Al were used as the active cathode, and there was a mathematical equation for the equilibrium potential and atomic radius of the alloy compounds formed with the lanthanides. [42][43][44] Further research shows that the equation could predict the equilibrium potentials of Al-An alloy compounds when Al as substrate metal. Therefore,…”
Section: Resultsmentioning
confidence: 97%
“…To ensure that the linear equation can be applied universally, we carried out experiments at 873, 923, 973 and 1023 K in the study of Pb-Ln intermetallic compounds. 42 The results show that the linear equation is not affected by temperature. The molten salt component we selected is LiCl-KCl system, Cl-based molten salts have been used as reaction media due to their properties such as their radiation resistance, short cooling time and proliferation resistance.…”
mentioning
confidence: 91%
“…Such a spherical confinement of hydrogen atom enables investigation of many properties in several studies [7]. A set of empirical atomic radii has been proposed and sum of the atomic radii of two atoms forming a bond in a crystal or molecule is used for estimation of approximate distance between nucleuses of those two atoms [8]. For other atoms and molecules, relationship between atomic radius and chemical properties has been investigated.…”
Section: Introductionmentioning
confidence: 99%